National Gods and Local Contexts: Distinguishing the Five Emperors and the Five Manifestations in Late Imperial China - Szonyi, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1995)
AbstractMany scholars of late imperial China have argued that the imperial state's sanctioning of certain cults was an important factor in the standardization of Chinese culture. This paper is a case study of the Five Emperors, a local cult which was not only not sanctioned, but actively suppressed by state officials. In response, worshippers of thecult concealed their deities behind the Five Manifestations, a cult which was state sanctioned. But the cult retained distinctive rituals, iconography, and representations in local popular culture. The conflation of the Five Emperors with other trans-local cultures demonstrates that the standardization of Chinese culture was often only illusory, concealing enduring local distinctiveness.